INCREASING WRITING MOTIVATION AND NARRATIVE WRITING ACHIEVEMENT OF ELEVENTH GRADERS OF SMAN 5 PALEMBANG BY USING ENGLISH ANIMATION FILMS - Budi Robintas (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2019)
In accordance with the problems faced by the eleventh graders in SMA Negeri 5 Palembang, this study is intended to increase the students’ writing motivation and narrative writing achievement by using English animation films as the instructional media. In this study, writing English narrative test and questionnaire were utilized as the research instruments. From 330 the eleventh graders, 66 of them were selected by using purposive sampling and divided into 2 groups; Experimental and Control. Based on the data analysis, the result showed that the use of English animation films significantly increased the students’ writing motivation and writing narrative texts achievement. Keywords: writing ability, writing motivation, narrative text, English animation films.